2018
DOI: 10.1016/j.jpedsurg.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of inpatient pediatric trauma in United States hospitals 2000 to 2011

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 50 publications
6
43
0
1
Order By: Relevance
“…Population-based studies have reported that yearly between 3% and 8% of children experience sports-related injuries (Bruhmann & Schneider, 2011; Sheu et al, 2016), and recent studies have indicated that sport-related injuries represent one third of all emergency department (ED) visits among school-age children (Harmon et al, 2018) and occur five times more frequently than those caused by injuries from road accidents (Finch et al, 2014). They are also the second most common cause of severe injuries such as traumatic brain or spinal cord in children over 10 years of age (Oliver et al, 2018). Increasing trends reported for traumatic brain (Bayt & Bell, 2016), internal organs (Bayt & Bell, 2016), severe knee (Shaw & Finch, 2017) and dental (James et al, 2018) injuries sustained by children while playing sports in the last decade have raised concerns among parents and pediatric health professionals in relation to their potential long-term consequences, particularly of severe injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies have reported that yearly between 3% and 8% of children experience sports-related injuries (Bruhmann & Schneider, 2011; Sheu et al, 2016), and recent studies have indicated that sport-related injuries represent one third of all emergency department (ED) visits among school-age children (Harmon et al, 2018) and occur five times more frequently than those caused by injuries from road accidents (Finch et al, 2014). They are also the second most common cause of severe injuries such as traumatic brain or spinal cord in children over 10 years of age (Oliver et al, 2018). Increasing trends reported for traumatic brain (Bayt & Bell, 2016), internal organs (Bayt & Bell, 2016), severe knee (Shaw & Finch, 2017) and dental (James et al, 2018) injuries sustained by children while playing sports in the last decade have raised concerns among parents and pediatric health professionals in relation to their potential long-term consequences, particularly of severe injuries.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by many previously published studies. 19,25,26,27 Unlike the previous studies 21,22,28 fall was not the most common injury mechanism, rather it was the second most common injury mechanism, 34.0 %( n=238). Vehicle related incidents are the most common injury mechanism in boys and fall is most common in girls.…”
Section: Discussionmentioning
confidence: 57%
“…Findings of this study are in accordance with literature that suggests there are certain types of injuries that are common in specific child age group. In a study on 2.4 million pediatric traumatic injury cases in the US from 2000–2011, motorcycle accidents were the most common mechanism of traumatic injuries for all age groups [ 24 ]. In children less than 5 years old, burns and abuse were the second and third most common causes of severe traumatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In children aged 5–9 years, falls and animal bites were the second and third most common causes of injuries. Sports were the second most common cause of injury in children aged 10–14 years [ 24 ]. This study also found the changing patterns of injuries with age.…”
Section: Discussionmentioning
confidence: 99%